A New Transformation Model of Electronic Waqf Management Using Barcode Scanning in Indonesia - Ong Argo Victoria; Siti Sumiati (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Virtual Payment through barcode scanning is one of the impacts of digitalization and modernization of technology in the field of payment management in various ways, which initially through the Transfer System (Manual Transfer; ATM; Mobile Banking etc.) to the Barcode System (QR Code; QRIS, Universal Product Code (UPC-A); EAN-13; Datamatrix etc.). Not to mention E-money and various E-Commerce Platforms providing electronic payment services such as OVO and GO-PAY, etc. they also use barcode scanning and are even considered more effective and considered easier by most people. Therefore, Waqf Management should also adapt to the development of world technology which is increasingly modern and more flexible, one of which is using the barcode scan above. Unfortunately, there are still many Waqf Managers (Nadzir) in Indonesia who still apply the Conventional Management System where they tend to maintain old habits in collecting funds from Waqf (Wakif) for certain reasons, both lack of understanding of religious doctrine and lack of ability to utilize current developments in information technology. This certainly causes the ineffectiveness of the Muslim community in Waqf Asset Management, especially the understanding of waqf assets (Mauquf) which is conservatively fixed (land/goods) to movable (money/cash), from the original tangible (real) to intangible (abstract/electronic/E-Waqf). In fact, Islamic countries are starting to change the conventional waqf asset management system to electronic waqf with the help of banking systems and types of payment systems, such as Kuwait, Qatar, the United Arab Emirates, Jordan, Saudi Arabia, Egypt, Turkey, Bangladesh and Malaysia. In Indonesia, digitalization in the financial sector has actually been supported by the government by launching the GNNT program aka the National Non-Cash Movement since 2014 but has not been realized optimally. In addition, Zakat, Infaq, Shodaqah (ZIS) has also begun to widely use barcode scanning even affixed to donation boxes and mosque walls. However, for waqf it is very minimal due to different conceptual understandings. Therefore, there is a need for wider socialization and increased financial inclusion so that the management of Islamic waqf funds becomes faster, more efficient, integrated, secure, controlled and cross-border. This thesis aims to; 1) To find out how the current condition of Electronic Waqf (E-Waqf) in Indonesia is. 2) To analyze the transformation model of Electronic Waqf Management (E-Waqf) via Barcode Scan in Indonesia. This research is a qualitative research with a descriptive analytical approach. The data collection technique used is a literature study, through books, scientific journals, websites, etc. In addition, interviews with several informants from sources as a reinforcement of research data. The data analysis technique uses qualitative analysis techniques that have four stages, namely data collection, data reduction, data presentation and the final step is drawing conclusions and verification. The results of this study are expected to transform Electronic Waqf Management (E-Wqf) in Indonesia to be more Modern, Accessible, Fast, Safe and Transparent through Virtual Payment via Scan Barcode as a medium for collecting waqf funds quickly and accurately while being directly supervised by the Indonesian Waqf Board (BWI) as the Organizer, Financial Institutions; Business Entities, and/or Communities that have been appointed to prevent misappropriation of funds. The ultimate goal is the creation of broader Community Welfare across borders in all walks of life.